Maternal dexamethasone treatment alters tissue and circulating components of the renin-angiotensin system in the pregnant ewe and fetus - Forhead, Alison J.; Jellyman, Juanita K.; De Blasio, Miles J.; Johnson, Emma; Giussani, Dino A.; Broughton Pipkin, Fiona; Fowden, Abigail L. (Endocrine Society, 2015)
Antenatal synthetic glucocorticoids promote fetal maturation in pregnant women at risk of preterm delivery and their mechanism of action may involve other endocrine systems. This study investigated the effect of maternal dexamethasone treatment, at clinically relevant doses, on components of the renin-angiotensin system (RAS) in the pregnanteweandfetus.From125 days of gestation (term, 145_2 d), 10 ewes carrying single fetuses of mixed sex (3 female, 7 male) were injected twice im, at 10–11 PM, with dexamethasone (2_12 mg, n_5) or saline (n_5) at 24-hour intervals. At 10 hours after the second injection, maternal dexamethasone treatment increased angiotensin-converting enzyme (ACE) mRNA levels in the fetal lungs, kidneys, and heart and ACE concentration in the circulation and lungs, but not kidneys, of the fetuses. Fetal cardiac mRNA abundance of angiotensin II (AII) type 2 receptor decreased after maternal dexamethasone treatment. Between the two groups of fetuses, there were no significant differences in plasma angiotensinogen or renin concentrations; in transcript levels of renal renin, or AIItype 1 or 2 receptors in the lungs and kidneys; or in pulmonary, renal or cardiac protein content of the AII receptors. In the pregnant ewes, dexamethasone administration increased pulmonary ACE and plasma angiotensinogen, and decreased plasma renin, concentrations. Some of the effects of dexamethasone treatment on the maternal and fetal RAS were associated with altered insulin and thyroid hormone activity. Changes in the local and circulating RAS induced by dexamethasone exposure in utero may contribute to the maturational and tissue-specific actions of antenatal glucocorticoid treatment.